D-003 (Saccharum officinarum): The forgotten lipid-lowering agent. (December 2016) - Awad, Kamal; Penson, Peter; Banach, Maciej
Graphical abstract: D-003 mechanism of action. Abstract: Reduction of elevated cholesterol levels, particularly low-density lipoprotein cholesterol (LDL-C), is essential in primary and secondary prevention of cardiovascular disease (CVD). Therefore there is still a large need for new effective drugs, which would be able to essentially reduce LDL-C and in the consequence CV residual risk. D-003 is a mixture of high aliphatic primary acids purified from sugarcane ( Saccharum officinarum ) wax. It showed promising hypocholesterolemic effects in both animal and human studies; it significantly lowers both serum total cholesterol (TC) and LDL-C, and increases high-density lipoprotein cholesterol (HDL-C). In addition, it showed a favorable safety profile. In this review, we evaluated the profile of D-003 as a lipid-lowering agent based on data from available preclinical and clinical studies.